Foreign exchange dealer asset pricing - Stefan Reitz; Dennis Umlandt (Deutsche Bundesbank, 2019)
We show that excess returns to the carry trade can be interpreted as compensation for foreign exchange dealers' capital risk. Given that the top market makers in foreign exchange are at the heart of the market's information aggregation process we also suggest that it is their marginal value of wealth which prices foreign currencies. Consistent with this hypothesis the empirical results show that shocks to the equity capital ratios of the top three foreign exchange dealers have explanatory power for the cross-sectional variation in expected currency market returns, while those of the average dealer provide no substantial additional information.
Keywords: F31; G12; G15; 330; Carry Trades; FX Dealers; Currency Risk; Intermediary Asset Pricing